Making aid work: Governance and decentralization - Gil S. Epstein; Ira N. Gang (Rutgers University, Department of Economics, 2015)
Donor aid organizations (DAOs) are multi-layered and multi-dimensional bureaucracies with many departments trying to find solutions to problems for countries, investing staff resources and effort into having an effect. A department may come into conflict with other departments because of personal and other rivalries, at least partly overlapping jurisdictions, and/or the bureaucratic necessity of laying claim to having the bigger impact. The idea here is that good governance starts at home. We consider how inter-departmental competition within the DAO affects departments' efforts and the DAO's performance measured by its ability to maximize effort towards helping a client country. In short, we wish to see how alternative reward systems which DAOs may put into place motivate competing departments in implementing the organization's goals. The argument for establishing good governance criteria is as much to put constraints on donor behavior as on the necessity of properly acting recipients.
Keywords: O10; O19; F35; 330; foreign aid; governance; rent seeking; decentralization